China its history and culture - Morton, W. Scott (William Scott) (McGraw-Hill, 1995)
A concise, illustrated survey of Chinese religion, philosophy, art, dynastic courts, militarism, and agriculture from ancient times to the present also considers those aspects of Chinese culture transformed by the Revolution of 1949.